Anti-swelling surface layer composite hydrogel as well as preparation method and application thereof
By forming a polyelectrolyte layer on the surface of the hydrogel and adjusting its swelling behavior, the problem of excessive swelling of the hydrogel in a humid environment is solved, and the stability and functionality of the biomedical field are maintained.
Patent Information
- Application Number
- CN202510384432.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing hydrogels are prone to excessive swelling in humid environments, resulting in a decrease in mechanical properties and an increase in interface tension, affecting their application in the field of biomedical medicine.
The design of anti-swelling surface composite hydrogel is adopted, including substrate material, hydrogel layer and polyelectrolyte layer. Through the formation of the polyelectrolyte layer, the swelling behavior of the hydrogel is adjusted, the swelling rate is slowed, and the interface tension is reduced.
Effectively control the swelling behavior of the hydrogel, maintain mechanical stability and functionality, and avoid excessive swelling. It is suitable for medical dressings, trauma repair and drug release systems and other applications.
Smart Images

Figure CN119912633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, and in particular to an anti-swelling surface composite hydrogel, a preparation method and application thereof. Background Art
[0002] Hydrogel is a type of hydrophilic polymer material with a three-dimensional network structure, which is widely used in medical, environmental, food and industrial fields. In the biomedical field, hydrogel is usually used as a drug delivery system, wound dressing, etc. However, due to its high swelling capacity, hydrogel may over-swell in the body or in a humid environment, resulting in a decrease in mechanical properties and even affecting adhesion to the substrate, resulting in adverse biological reactions. Therefore, how to effectively control the swelling behavior of hydrogel, slow down its swelling rate, and avoid interfacial tension caused by swelling is a key technical problem in the application of hydrogel materials in the biomedical field.
[0003] At present, some studies have tried to adjust the swelling properties of hydrogels by changing the cross-linking degree of hydrogels or adding different fillers to hydrogels. However, these methods often find it difficult to maintain the good functionality and biocompatibility of hydrogels while controlling the swelling behavior. Therefore, there is an urgent need for a new technical means that can effectively control the swelling of hydrogels and ensure their stability and functionality during application.
[0004] At present, in the research on anti-swelling hydrogels, some technical solutions have been proposed to solve the above problems, but there are still certain limitations.
[0005] Chinese invention patent application CN202011427315.6 discloses a high-strength multi-level hydrogel and its preparation method and application. After adding a first strong acid solution or a first metal ion solution to the polyelectrolyte solution, the solution is frozen to obtain a hydrogel; after thawing the obtained hydrogel, the solution is immersed in a second strong acid solution or a second metal ion solution, washed, and the hydrogel is obtained. Although this hydrogel has made breakthroughs in mechanical properties, the process involves immersion in a strong acid solution, which will irritate the surface of biological tissues and is not suitable for use on human skin.
[0006] Chinese invention patent application CN202110814384.0 discloses a polyelectrolyte hydrogel coating with super strong substrate adhesion performance and its preparation method. This scheme adopts a mixed polycationic polymer, a polymer monomer, a siloxane crosslinker and an initiator to obtain a prepolymer solution, which is vacuumed to remove bubbles and then coated on the surface of the substrate activated by oxygen plasma. It is in situ polymerized under a nitrogen or rare gas atmosphere and cured to form a hydrogel coating. This composite coating can be widely used in medical devices to improve strong adhesion, and the coating can be firmly bonded to the surface of medical devices. However, the defect of this scheme is that the hydrogel cannot control swelling in a liquid environment, the overall mechanical properties are reduced, and the adhesion stability cannot be guaranteed.
[0007] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0008] The purpose of the present invention is to solve the problem of how to effectively control the swelling behavior of hydrogel, slow down its swelling rate, and avoid the interfacial tension caused by swelling, and provide an anti-swelling surface composite hydrogel, a preparation method and an application thereof.
[0009] In order to achieve the above object, the present invention discloses an anti-swelling surface composite hydrogel, comprising a base material, a hydrogel layer, and a polyelectrolyte layer, wherein the hydrogel layer is arranged on the base material, and the polyelectrolyte layer covers the surface of the hydrogel layer.
[0010] The material of the polyelectrolyte layer is any one or more combinations of polyacrylic acid, polyvinyl alcohol, polyamino acid, polyethyleneimine and derivatives thereof.
[0011] The thickness of the polyelectrolyte layer is 1 nm to 500 μm.
[0012] The substrate material is a biocompatible material, which is any one or more combinations of metals, ceramics, polymers, natural materials and composite materials thereof.
[0013] The hydrogel layer is any one or more combinations of polyacrylamide-based hydrogel, poly(acrylic acid)-based hydrogel, and poly(N,N-dimethylacrylamide)-based hydrogel.
[0014] The present invention also discloses the anti-swelling surface composite hydrogel, which comprises the following steps:
[0015] S1, performing surface treatment on the selected substrate material to ensure that the hydrogel layer can be evenly bonded to the substrate material;
[0016] S2, mixing the selected hydrogel precursor, auxiliary agent and solvent to obtain a hydrogel precursor solution, and forming a hydrogel layer on the substrate material by solution polymerization or other cross-linking methods;
[0017] S3, infiltrating the polyelectrolyte solution into the surface of the hydrogel layer to form a polyelectrolyte layer;
[0018] S4, curing the polyelectrolyte layer to control the swelling behavior of the hydrogel.
[0019] In step S3, the penetration method is any one of immersion, spraying or coating, and the immersion time is 2 to 12 hours.
[0020] In step S4, the curing method is any one of chemical crosslinking, heat treatment or light curing; the concentration of the crosslinking agent of the chemical crosslinking is 1% to 80%, and the crosslinking reaction time is 10 min to 24 h; the temperature of the heat treatment is 40°C to 150°C, and the time is 5 min to 100 min.
[0021] The invention also discloses the application of the anti-swelling surface composite hydrogel in medical dressings and wound repair.
[0022] The invention also discloses the application of the anti-swelling surface composite hydrogel in a drug release system and a biomedical sensor.
[0023] The polyelectrolyte forms a dense ion-crosslinked surface layer with the hydrogel surface, regulating the swelling of the hydrogel through the formation of a semipermeable barrier and other mechanisms, which limits the influx of water and reduces the osmotic pressure. This anti-swelling mechanism prevents the hydrogel from exerting excessive pressure on the wound when used in a wet environment, allowing it to stably adhere to the wound and provide effective protection.
[0024] The surface composite hydrogel swelling control material of the present invention comprises a base material, a hydrogel layer bonded to the base material, and a polyelectrolyte layer whose swelling is controlled by a polyelectrolyte layer. The base material provides good mechanical support, and the hydrogel layer, as a high-water-containing functional module, controls swelling while maintaining its high hydrophilicity and biocompatibility, while the polyelectrolyte layer serves as an interface regulating layer, effectively slowing down the swelling rate of the hydrogel and reducing the interfacial tension caused by swelling. Through this structural design, the hydrogel swelling control material of the present invention can maintain good mechanical stability and functionality in a humid environment, avoiding the problem of excessive swelling of traditional hydrogels in biomedical applications.
[0025] Compared with the prior art, the present invention has the following beneficial effects: the present invention effectively controls the swelling behavior of the hydrogel by forming a polyelectrolyte layer on the surface of the hydrogel, thereby avoiding the degradation of mechanical properties and interfacial tension problems caused by swelling; the formation of the polyelectrolyte layer does not interfere with the basic composition of the hydrogel, and can maintain the biocompatibility and functionality of the hydrogel; the method is simple and easy, and has good controllability, and is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a front swelling photograph of the poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel bonded to a glass substrate prepared in Comparative Example 1 of the present invention;
[0027] Figure 2This is a side swelling photograph of the poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel bonded to a glass substrate prepared in Comparative Example 1 of the present invention;
[0028] Figure 3 This is a front swelling photograph of the poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel bonded to a glass substrate prepared in Comparative Example 2 of the present invention;
[0029] Figure 4 This is a side swelling photograph of the poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel bonded to a glass substrate prepared in Comparative Example 2 of the present invention;
[0030] Figure 5 Schematic diagram of the swelling modes of poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel and poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Comparative Examples 1 and 2 of the present invention;
[0031] Figure 6 It is a curve diagram of the mass swelling rate of poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel and poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Comparative Examples 1 and 2 of the present invention as a function of time;
[0032] Figure 7 It is a graph showing the change of thickness swelling rate over time of poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel and poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Comparative Examples 1 and 2 of the present invention;
[0033] Figure 8 This is a front swelling photograph of the poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Example 1 of the present invention and bonded to a glass substrate after being surface-compounded with a polyacrylic acid layer;
[0034] Fig. 9This is a side swelling photograph of the poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Example 1 of the present invention and bonded to a glass substrate after being composited with a polyacrylic acid surface layer;
[0035] Fig.10 This is a front swelling photograph of the poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Example 2 of the present invention and bonded to a glass substrate after being surface-compounded with a polyacrylic acid layer;
[0036] Fig.11 This is a side swelling photograph of the poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Example 2 of the present invention and bonded to a glass substrate after being composited with a polyacrylic acid surface layer;
[0037] Fig.12 Schematic diagram of the swelling mode of poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel and poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Examples 1 and 2 of the present invention after being compounded with a polyacrylic acid surface layer;
[0038] Fig.13 The mass swelling rate of poly(acrylamide (AM)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel and poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyltrimethylammonium chloride (METAC)) copolymer hydrogel prepared in Examples 1 and 2 of the present invention after being compounded with a polyacrylic acid surface layer is a curve chart of changes over time. The slash in the horizontal axis is the breakpoint processing in the chart processing. The reason for the breakpoint processing is as follows: only a few time points (i.e., the time points marked on the horizontal axis) are taken for testing in the figure, and no sampling test is performed on the time points among the several time points. For the beauty of the chart, the breakpoint processing is used to shorten the distance between the test time points;
[0039] Fig.14The thickness swelling rate of poly(acrylamide (AM)-co-methacryloyloxyethyl trimethyl ammonium chloride (METAC)) copolymer hydrogel and poly(N,N-dimethylacrylamide (DMA)-co-methacryloyloxyethyl trimethyl ammonium chloride (METAC)) copolymer hydrogel prepared in Examples 1 and 2 of the present invention after being compounded with a polyacrylic acid surface layer is a curve chart of changes over time. The slash in the horizontal axis is the breakpoint processing in the chart processing. The reason for the breakpoint processing is as follows: only a few time points (i.e., the time points marked on the horizontal axis) are taken for testing in the figure, and no sampling test is performed on the time points among the several time points. For the beauty of the chart, the breakpoint processing is used to shorten the distance between the test time points;
[0040] Fig.15 The finite element simulation schematic diagram and the interface stress accumulation analysis diagram of the present invention, wherein: (a) the first stage represents the initial stress distribution; (b) the second stage shows the stress concentration formed as the swelling begins; (c) the third stage depicts the expansion of the stress concentration as the swelling further develops; (d) the distribution of the substrate tangential stress at different swelling stages; (e) the distribution of the interface tangential stress at different swelling stages; (f) the distribution of the hydrogel tangential stress at different swelling stages; (g) the distribution of the substrate normal stress at different swelling stages; (h) the distribution of the interface normal stress at different swelling stages; (i) the distribution of the hydrogel normal stress at different swelling stages;
[0041] Fig.16 It is a graph showing the thickness of the polyelectrolyte layer in Examples 3, 4 and 5 of the present invention;
[0042] Fig.17 Statistical graph of polyelectrolyte layer thickness in Example 3, Example 4 and Example 5 of the present invention;
[0043] Fig.18 This is a graph showing different swelling rates corresponding to different immersion times of the polyelectrolyte in Example 3, Example 4 and Example 5 of the present invention. DETAILED DESCRIPTION
[0044] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0045] Example 1
[0046] Use a plasma machine to modify the clean glass surface to make it hydrophilic.
[0047] Mix glacial acetic acid and deionized water, and adjust the pH value of the mixed solution to 3.5. Mix KH570 and glacial acetic acid in a ratio of 1:50, put into an ultrasonic cleaning machine, and enter emulsification. Soak the hydrophilic modified glass in the emulsified solution for 2 hours for silanization modification.
[0048] Acrylamide monomer, methacryloyloxyethyl trimethyl ammonium chloride monomer, initiator 2-hydroxy-2-methylacetophenone, and crosslinker methylene bisacrylamide were dissolved in deionized water to prepare poly N,N-dimethylacrylamide hydrogel precursor solution. 3 The silicone mold was attached to the treated substrate, the precursor solution was poured into the mold, and the mold was placed in a 365 nm UV box for photocuring for 1 hour to obtain poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel.
[0049] The concentrations of N,N-dimethylacrylamide monomer, methacryloyloxyethyltrimethylammonium chloride monomer, initiator 2-hydroxy-2-methylacetophenone, and cross-linking agent methylenebisacrylamide are 5%, 0.1%, and 0.01%, respectively.
[0050] The prepared poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel was immersed in a polyelectrolyte solution at 50°C for 12 hours to obtain a poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer (named PAA@P(AAM-co-METAC)).
[0051] The polyelectrolyte solution is a polyacrylic acid aqueous solution with a molecular weight of 3000 and a concentration of 30 wt%.
[0052] Under the conditions of Example 1, the poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer exhibited excellent anti-swelling ability. Figure 1 , 2 As shown in Figures 5-7, the weight swelling ratio of polyacrylamide hydrogel without polyelectrolyte modification reached 31 times after swelling for 1 day, but it could not maintain its shape after that, lost its mechanical and adhesive properties, and fell off the substrate. Figure 8 , 9 As shown in Figures 12-14, the poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer was subjected to a swelling experiment. After swelling in water for 7 days, the poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer was still able to maintain its complete shape, and the weight and volume swelling ratios reached 1.2 times and 1.5 times, respectively, and it was able to firmly adhere to the substrate. Fig.15In the figure, (a) to (i) reveal the three-stage evolution of stress during hydrogel swelling: initial stress distribution, stress concentration formation, and stress concentration expansion. In stage 1, stress is uniformly distributed in the hydrogel and the interface. However, as swelling enters stage 2, stress begins to localize at the interface edge, driven by the limited swelling force. By stage 3, the edge stress concentration is significantly enhanced, accompanied by the onset of interface delamination at 0.6 seconds. This delamination indicates that the swelling-induced stress at the edge exceeds the interfacial bonding strength, leading to failure. Both tangential stress and normal stress contribute to the mechanical instability of the hydrogel, and the tangential stress curve shows a sharp increase in stress at the edge, which tends to stabilize after reaching a peak. The normal stress curve shows a similar edge concentration, but its rise is more extensive and gradually increases, especially in the hydrogel and interface regions. Importantly, the normal stress also increases significantly at the center of the interface, while the tangential stress remains at a low level. This suggests that swelling-induced stress affects not only the local edge region but also the center region of the interface, which may endanger the overall stability of the hydrogel system.
[0053] Example 2
[0054] Use a plasma machine to modify the clean glass surface to make it hydrophilic.
[0055] Mix glacial acetic acid and deionized water, and adjust the pH value of the mixed solution to 3.5. Mix KH570 and glacial acetic acid in a ratio of 1:50, put into an ultrasonic cleaning machine, and enter emulsification. Soak the hydrophilic modified glass in the emulsified solution for 2 hours for silanization modification.
[0056] N,N-dimethylacrylamide monomer, methacryloyloxyethyl trimethylammonium chloride monomer, initiator 2-hydroxy-2-methylacetophenone, and crosslinker methylenebisacrylamide were dissolved in deionized water to prepare poly(N,N-dimethylacrylamide-co-methacryloyloxyethyl trimethylammonium chloride) hydrogel precursor solution. 3 The silicone mold was attached to the treated substrate, the precursor solution was poured into the mold, and the mold was placed in a 365 nm UV box for photocuring for 1 hour to obtain poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel.
[0057] The concentrations of N,N-dimethylacrylamide monomer, methacryloyloxyethyltrimethylammonium chloride monomer, initiator 2-hydroxy-2-methylacetophenone, and cross-linking agent methylenebisacrylamide are 5%, 0.1%, and 0.01%, respectively.
[0058] The prepared poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel was immersed in a polyelectrolyte solution at 50°C for 12 hours to obtain a poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer (named PAA@P(DMA-co-METAC)).
[0059] The polyelectrolyte solution is a polyacrylic acid aqueous solution with a molecular weight of 3000 and a concentration of 30 wt%.
[0060] Under the conditions of Example 2, the poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer exhibited excellent anti-swelling ability. Figure 3 , 4 As shown in Figure 5, the swelling ratio of the poly (N,N-dimethylacrylamide) hydrogel not modified with polyelectrolyte reached 51 times after swelling for 1 day, and it could not maintain its shape, lost its mechanical properties, and fell off the substrate. The huge swelling caused huge stress at the interface between the substrate and the hydrogel, and the stress accumulation caused the hydrogel's adhesive properties to fail. Figure 8 , 9 As shown in Figures 10 and 11, the poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer was subjected to a swelling experiment. After swelling in water for 7 days, the poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer was still able to maintain its complete shape, and the weight and volume swelling ratios reached 1.8 times and 2.8 times, respectively. After soaking in water for 7 days, the poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer was still able to firmly adhere to the substrate, while the poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel without polyelectrolyte modification fell off quickly within just 24 hours. This shows that the poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer has great application potential in wet environments.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that the immersion time of the polyelectrolyte solution is 2 hours, and the other process conditions are the same as those of embodiment 1, and a poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer (named as P-2 h) is obtained.
[0063] Example 4
[0064] The difference between this embodiment and embodiment 1 is that the immersion time of the polyelectrolyte solution is 4 hours, and the other process conditions are the same as those of embodiment 1, thereby obtaining a poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer (named as P-4 h).
[0065] Example 5
[0066] The difference between this embodiment and embodiment 1 is that the immersion time of the polyelectrolyte solution is 12 hours, and the other process conditions are the same as those of embodiment 1, and a poly(acrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel with a polyelectrolyte layer (named as P-12 h) is obtained.
[0067] like Fig.16 , 17 As shown in Figures 18, the electrolyte immersion time is 2, 4, and 12 hours, the thickness of the polyelectrolyte layer is approximately 107.33333, 264.66667, and 305.33333 μm, and the swelling ratios after 24 hours of swelling are 6, 2, and 1.5, respectively. It can be seen that the thicker the polyelectrolyte layer, the better the anti-swelling performance. However, if the polyelectrolyte layer is too thick, the material will lose its adhesion properties. Therefore, the thickness of the polyelectrolyte layer needs to be controlled below 500 μm.
[0068] Comparative Example 1
[0069] Acrylamide monomer, methacryloyloxyethyl trimethyl ammonium chloride monomer, initiator 2-hydroxy-2-methylacetophenone, and crosslinker methylene bisacrylamide were dissolved in deionized water to prepare poly (acrylamide-co-methacryloyloxyethyl trimethyl ammonium chloride) hydrogel precursor solution. 3 The mold was attached to the treated substrate, and the precursor solution was poured into the mold and placed in a 365 nm UV box for photocuring for 1 h to obtain poly(acrylamide- co -methacryloyloxyethyltrimethylammonium chloride) hydrogel (named P(AAM- co -METAC)).
[0070] Comparative Example 2
[0071] N,N-dimethylacrylamide monomer, methacryloyloxyethyl trimethylammonium chloride monomer, initiator 2-hydroxy-2-methylacetophenone, and crosslinker methylenebisacrylamide were dissolved in deionized water to prepare poly(N,N-dimethylacrylamide-co-methacryloyloxyethyl trimethylammonium chloride) hydrogel precursor solution. 3The silicone mold was attached to the treated substrate, and the precursor solution was poured into the mold, which was placed in a 365 nm UV box for photocuring for 1 h to obtain poly(N,N-dimethylacrylamide-co-methacryloyloxyethyltrimethylammonium chloride) hydrogel (named P(DMA- co -METAC)).
[0072] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. Anti-swelling surface composite hydrogel, characterized in that: The invention comprises a base material, a hydrogel layer and a polyelectrolyte layer. The hydrogel layer is arranged on the base material, and the polyelectrolyte layer covers the surface of the hydrogel layer.
2. The anti-swelling surface composite hydrogel according to claim 1, characterized in that: The material of the polyelectrolyte layer is any one or more combinations of polyacrylic acid, polyvinyl alcohol, polyamino acid, polyethyleneimine and derivatives thereof.
3. The anti-swelling surface composite hydrogel according to claim 1, characterized in that: The thickness of the polyelectrolyte layer is 1 nm to 500 μm.
4. The anti-swelling surface composite hydrogel according to claim 1, characterized in that: The substrate material is a biocompatible material, which is any one or more combinations of metals, ceramics, polymers, natural materials and composite materials thereof.
5. The anti-swelling surface composite hydrogel according to claim 1, characterized in that: The hydrogel layer is any one or more combinations of polyacrylamide-based hydrogel, poly(acrylic acid)-based hydrogel, and poly(N,N-dimethylacrylamide)-based hydrogel.
6. The method for preparing the anti-swelling surface composite hydrogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, performing surface treatment on the selected substrate material to ensure that the hydrogel layer can be evenly bonded to the substrate material; S2, mixing the selected hydrogel precursor, auxiliary agent and solvent to obtain a hydrogel precursor solution, and forming a hydrogel layer on the substrate material by solution polymerization or other cross-linking methods; S3, infiltrating the polyelectrolyte solution into the surface of the hydrogel layer to form a polyelectrolyte layer; S4, curing the polyelectrolyte layer to control the swelling behavior of the hydrogel.
7. The method for preparing the anti-swelling surface composite hydrogel according to claim 6, characterized in that: In step S3, the penetration method is any one of immersion, spraying or coating, and the immersion time is 2 to 12 hours.
8. The method for preparing the anti-swelling surface composite hydrogel according to claim 6, characterized in that: In the step S4, the curing method is any one of chemical crosslinking, heat treatment or light curing; the concentration of the crosslinking agent of the chemical crosslinking is 1% to 80%, and the crosslinking reaction time is 10 min to 24 h; the temperature of the heat treatment is 40°C to 150°C, and the time is 5 min to 100 min.
9. Use of the anti-swelling surface composite hydrogel according to any one of claims 1 to 5 in medical dressings and wound repair.
10. Use of the anti-swelling surface composite hydrogel according to any one of claims 1 to 5 in drug release systems and biomedical sensors.
Citation Information
Patent Citations
Piezoresistive sensor material and preparation method and application thereof
CN110776667A
Polyelectrolyte hydrogel coating with super-strong substrate adhesion performance and preparation method of polyelectrolyte hydrogel coating
CN113842507A
Swelling enhanced polyampholyte hydrogel and preparation method thereof
CN114835919A
Anti-electrostatic shielding gradient polyelectrolyte hydrogel, preparation method and application
CN118620271A
Adhesive hydrogel and method of manufacturing the same, composition for manufacturing adhesive hydrogel, and gel sheet
JP2012197343A